Semi-automatic algorithm for construction of the left ventricular area variation curve over a complete cardiac cycle - Melo Júnior, Salvador Alves de (2010)
The present study was supported by CNPq, a Brazilian government agency for scientific and technological development: “Chamada Conjunta MCT/SEPIN-FINEP-CNPq 01/2002, Programa de Apoio à Pesquisa e Desenvolvimento e Inovação em Tecnologia da Informação PDI - TI”. BM received a M.Sc. fellowship from the Brazilian Ministry of Education (MEC/CAPES).